Impact of insurance status and distance from residence to treatment center on the outcomes of patients diagnosed with acute myeloid leukemia - Mahmoud, Maya; Al Mahmasani, Layal; Charafeddine, Maya; Zahreddine, Ammar; Moukalled, Nour; El Cheikh, Jean; Bazarbachi, Ali; Abou Dalle, Iman (Frontiers in Hematology, 2022)
Purpose: Numerous factors may affect the survival outcomes of patients with acute myeloid leukemia (AML), mainly disease-related and treatment-related factors. The impact of other factors, such as the insurance status and the distance to healthcare facilities, are still unclear and may differ between different healthcare systems. We investigated the effects of insurance status and distance to the treatment center on the survival of AML patients. Materials and Methods: This is a single-center, observational, retrospective study of patients diagnosed with AML (2015–2020) and treated at the American University of Beirut Medical Center in Lebanon. Data regarding patient baseline characteristics, disease-related factors, insurance status, and area of residence were collected. Multivariate Cox regression analysis was used to identify main independent predictors of overall survival (OS). Results: We identified 142 AML patients with a median age of 52 years (range 18–86). Of them, 91 (64%) were males, 77 (54%) had ELN intermediate risk, and 88 (62%) patients received intensive chemotherapy. After a median follow-up of 22.4 months, the median RFS and OS were 37.4 months and not reached, respectively. A Cox regression model for OS was done using the following variables: age, gender, body mass index, comorbidities, smoking status, insurance status, distance from the center, ELN classification, treatment used, and allotransplant. A higher risk of death was seen among the uninsured patients and those living beyond 40 km from the treatment center compared with fully insured patients and those living in proximity to the center (hazard ratio [HR]: 3.65; 95% CI [1.79, 7.45], p-value <0.0001; HR: 4.38; 95% CI [1.75, 10.95], p-value 0.002, respectively). Conclusions: The outcome of patients with AML does not depend only on disease-related factors, as the insurance status and the distance from the area of residence to the treatment center were found to be independent predictors of survival in AML patients.